Bretton Woods II and the emerging economies: Lazarus, Phoenix, or Humpty Dumpty? - Arslan Razmi (University of Massachusetts, Department of Economics, 2009)
Several studies have commented on the emergence of a new international monetary system in the post-Asian crisis years. The current international financial crisis has, however, put Bretton Woods II under considerable strain. This paper analyzes the sustainability of the precrisis order from an emerging country perspective. A simple framework in which agents have a choice between financial and real assets is constructed in order to explore possible consequences of the shocks that emerging economies are currently experiencing. Stock and flow implications are analyzed. Assuming that recent events would have reinforced monetary authorities.desire to maintain an adequate cushion of reserves while preventing exchange rate volatility, we find that the response to most shocks would involve running continuous current account surpluses, that is, a continuation of a crucial aspect of Bretton Woods II. Given political and economic constraints, is such a continuation feasible? A preliminary exploration raises serious doubts and skims alternatives.
Keywords: F02; F32; G01; F55; 330; Bretton Woods II; emerging economies; reserve accumulation; precautionary motives; mercantilism